2003
DOI: 10.1074/mcp.m200051-mcp200
|View full text |Cite
|
Sign up to set email alerts
|

Protein Profiling of the Human Epidermis from the Elderly Reveals Up-regulation of a Signature of Interferon-γ-induced Polypeptides That Includes Manganese-superoxide Dismutase and the p85β Subunit of Phosphatidylinositol 3-Kinase

Abstract: Aging of the human skin is a complex process that consists of chronological and extrinsic aging, the latter caused mainly by exposure to ultraviolet radiation (photoaging). Here we present studies in which we have used proteomic profiling technologies and two-dimensional (2D) PAGE database resources to identify proteins whose expression is deregulated in the epidermis of the elderly.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
25
0
1

Year Published

2004
2004
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(28 citation statements)
references
References 108 publications
2
25
0
1
Order By: Relevance
“…For example, older human skin expresses reduced levels of certain proteins, including manganese-superoxide dismutase, tryptophanyl-tRNA synthetase, the p85ß subunit of phosphatidylinositol 3-kinase, and proteasomal proteins PA28-α (Gromov et al 2003). In rats, peroxiredoxin-2, an antioxidant enzyme, is able to be induced by irradiation in cultured astrocytes from young but less so from old rats (Miura et al 2007).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, older human skin expresses reduced levels of certain proteins, including manganese-superoxide dismutase, tryptophanyl-tRNA synthetase, the p85ß subunit of phosphatidylinositol 3-kinase, and proteasomal proteins PA28-α (Gromov et al 2003). In rats, peroxiredoxin-2, an antioxidant enzyme, is able to be induced by irradiation in cultured astrocytes from young but less so from old rats (Miura et al 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Proteomic techniques including two-dimensional gel electrophoresis (2-DE) have been used to study aging (Ballesteros et al 2001;Gromov et al 2003;Sato et al 2006;Miura et al 2007) and have led to the identification of many candidate proteins that are altered by aging. For example, older human skin expresses reduced levels of certain proteins, including manganese-superoxide dismutase, tryptophanyl-tRNA synthetase, the p85ß subunit of phosphatidylinositol 3-kinase, and proteasomal proteins PA28-α (Gromov et al 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, we previously reported that the radiation adaptive response observed in the astrocytes of young rats is suppressed in aged rats, indicating that the response of astrocytes to low-dose radiation decreases with age [12]. Thus, we tried to clarify the response of astrocytes to oxidative stress and its variation with age through proteomic analysis.Proteomic analysis offers great potential for studies on cellular protein alterations in various disease states [13][14][15], aging [16][17][18][19], and under oxidative stress [20][21][22][23][24]. Unlike genomic and transcriptional profiling, proteomic Age-dependent variation in cell responses to oxidative stress 2787 profiles can detect not only native proteins but also posttranslational modified species, which are the functional components in biological systems.…”
mentioning
confidence: 99%
“…Nine of the genes are down-regulated in BRCA2-ablated cells whereas five of them are up-regulated ( Table 1). Majority of the down-regulated genes are known to be regulated by interferons, e.g., tryptophanyl-tRNA synthetase, UCRP, UBE2L6, and Cig5 [22][23][24][25][26]. Interferons enhance cellular susceptibility to apoptosis in a variety of tumor cells [27].…”
Section: Down-regulation Of Ucrp Ube2l6 and Other Transcripts In Brmentioning
confidence: 99%